Armazenamento de sementes e produção de mudas de cedro (Cedrela odorata L.) - (:unkn) unknown (Universidade Federal do Amazonas, 2009)
With the growing demand for information on species with potential for use in restoration of degraded ecosystems and other forestry programs, it is crucial to understand the behavior of seeds in terms of storage and performance of the species due to the conditions of the substrate. The aim of this study was to evaluate the quality of stored seeds under different conditions to examine the growth of cedar seedlings in different combinations of correction and fertilization of the substrate. For this two experiments were conducted, one in the seed laboratory I and others in the seedling nursery of the Faculty of Agrarian Sciences, Federal University of Amazonas. Experiment I (storage of seeds), seeds were stored for 3 periods (3, 6 and 9 months) plus the control, and packed in 2 types of packaging (polyethylene and paper) and 2 types of environment (refrigerator and natural environment), arranged in a completely randomized design with factorial arrangement of 3x2x2 +1, distributed in 5 replications of 20 seeds. At the end of each period, we determined the percentage of seed germination and seedling normal. Means were compared by Tukey test at 5% probability for the interaction effect became the disaggregation of data, and for the storage periods were adjusted equations. Experiment II (formation of seedlings), were tested 8 treatments: T1 (cattle), T2 (lime), T3 (corrective phosphate), T4 (NPK), T5 (Cal + FC), T6 (FC + NPK), T7 (Cal + NPK) and T8 (Cal + FC + NPK), arranged in a completely randomized design with 4 replications for a total of 32 plots, each plot with 3 plants. At 100 days after the inoculation were analyzed: shoot height, stem diameter, leaf number, leaf area, dry matter of shoot, root and total, and the nutrient content in dry matter of shoots. Means were compared by Tukey test at 5% probability. The results indicated that seeds stored in the natural condition showed a drastic reduction in germination and normal seedling over the period of storage, while the condition of the refrigerator reduction was less intense. The type of packaging there was no effect, regardless of the type of storage environment. Regarding the formation of seedlings, cedar responded positively to the addition of manure, with the best values of nutrient content and vegetative growth. As for the other treatments, the effects were less important compared to cattle, however in terms of values to the isolated application of lime had the lowest results. Thus, we conclude that the condition was more efficient refrigerator to preserve the germination and vigor of trees, and for the formation of seedlings adding manure proves its efficiency in the supply of nutrients and plant growth.
Keywords: Produção de mudas; Recomposição de ecossistemas; Germinação de sementes - Cedro; Seedling formation; Substrate; CIÊNCIAS AGRÁRIAS